Multi-Partner Project: Sports Performance and Health Assessment in the DistriMuse Project - Davoli, Luca; Belli, Laura; Mattioli, Veronica; Raheli, Riccardo; Ferrari, Gianluigi; Priano, Lorenzo; Hubalek, Jaromir; Smital, Lukas; Nemcova, Andrea; Chlibkova, Daniela; Benes, Vlastimil; Plomp, Johan (Proceedings - Design, Automation, and Test in Europe Conference and Exhibition, 2025)
In our increasingly tech-saturated world, from mobile apps and health sensors to autonomous cars and factory robots, we expect these devices to seamlessly integrate into our lives, enhancing safety and convenience. However, as these devices proliferate and their autonomy grows, ensuring they provide unobtrusive, yet effective support becomes crucial. The Horizon Europe KST multi-partner project "Distributed Multi-Sensor Systems for Human Safety and Health" (DistriMuSe) intends to support human health and safety by improved sensing of human presence, behaviour, and vital signs in a collaborative or common environment by means of multi-sensor systems, distributed processing and MachinelDeep Learning (ML/DL) techniques. In this paper, we focus on the DistriMuSe's approach on sports performance and health assessment, focusing on monitoring the physical activity of non-professional and hobby athletes, people who like sports and care about their health, elderly healthy people, and subjects affected by neurological disability (e.g., Parkinson's disease). The overall goal is to measure activity and exertion, estimating performance levels and determining maximum effort. We discuss the overall system-of-systems architecture, focusing on the adopted technologies.